An engineered fibrinogen variant AαQ328,366P does not polymerise normally, but retains the ability to form α cross-links - Park, Rojin; Ping, Lifang; Song, Jaewoo; Seo, Joo-Young; Choi, Tae-Youn; Choi, Jong-Rak; Gorkun, Oleg V.; Lord, Susan T. (Thrombosis and Haemostasis, 2013)
A fibrin clot is stabilised through the formation of factor XIIIa-catalysed intermolecular ε -lysyl-γ -glutamyl covalent cross-links between α chains to form α polymers and between γ chains to form γ dimers. In a previous study we characterised fibrinogen Seoul II, a heterozygous dysfibrinogen in which a cross-linking acceptor site in Aα chain, Gln328, was replaced with Pro (AαQ328P). Following on the previous study, we investigated whether the alteration of Gln residues Aα328 and Aα366 affects fibrin polymerisation and α chain cross-linking. We have expressed three recombinant fibrinogens: AαQ328P, AαQ366P, and AαQ328,366P in Chinese hamster ovary cells, purified these fibrinogens from the culture media and performed biochemical tests to see how the introduced changes affect fibrin polymerisation and α chain cross-linking. Thrombin-catalysed fibrin polymerisation of all variants was impaired with the double mutation being the most impaired. In contrast, sodium dodecyl sulfate–polyacrylamide gel electrophoresis and immunoblot analysis showed α polymer formation with all three engineered proteins. This study demonstrates that AαQ328 and AαQ366 are important for normal fibrin clot formation and in the absence of residues AαQ328 and AαQ366, other Gln residues in the a chain can support FXIIIa-catalysed fibrin cross-linking.
Keywords: Fibrin alpha chain; cross-linking; Glutamine acceptor; AαQ328; AαQ366